"Bild des Bildlosen": das Bilderverbot und das Bekenntnis zur Selbstoffenbarung Gottes in Jesus von Nazareth - Wendel, Saskia (Zeitschrift für katholische Theologie, 2011)
How to imagine the unimaginable? The biblical prohibition to form an image of God runs counter to the power of images and words, and against the - also biblical - notion of Christ as the icon of God. Understood as an invitation to approach any image of God with a critical consciousness, the prohibition runs against the need to explain what the grounds for its critique are. The study examines a num- ber of modern authors dealing with this problem in order to sharpen the dialectic between the image and the unimaginable reality it refers to, namely the reality of the Absolute.